Tracking the Economic Benefits Generated by the Hard Clam Aquaculture Industry in Florida - Charles Adams; Leslie Sturmer; Alan Hodges (EDIS)
The hard clam industry is a true success story for commercial aquaculture in Florida. From a cottage industry borne of reductions in commercial wild clam harvests in the Indian River Lagoon during the late 1980s, hard clam aquaculture has now developed into an industry that is rivaled by no other aquaculture food product in Florida. Although successful by virtually any metric, the risks and uncertainty associated with commercial hard clam culture has led to the evaluation of programs that help mitigate risk, such as the former pilot Cultivated Clam Crop Insurance Program administered by USDA Risk Management Agency. All of this alludes to the economic importance of the hard clam culture industry which, through the cultivation process and sales of products, generates local income and taxes, creates jobs and businesses, and draws new money into the local economy, as cultured hard clams are sold to non-residents and buyers outside the region and state. This 6-page fact sheet provides an overview of a recent study by the University of Florida to provide an estimate of the impact of the hard clam industry to the Florida economy. Written by Charles Adams, Leslie Sturmer, and Alan Hodges, and published by the UF Department of Food and Resource Economics, October 2014. (UF/IFAS photo by Tom Wright).